Lymphocytes in Alzheimer’s Disease Pathology: Altered Signaling Pathways - Esteras, Noemí; Alquézar, Carolina; de la Encarnación, Ana; Martín-Requero, æ#129;ngeles (Current Alzheimer Research, 2016)
Alzheimer’s disease (AD) is a neurodegenerative disorder marked by progressive impairment of cognitive ability. Patients with AD display neuropathological lesions including plaques, neurofibrillary tangles, and neuronal loss in brain regions linked to cognitive functions. Despite progress in uncovering many of the factors that contribute to the etiology of this disease, the cause of neuronal death is largely unknown. Neuroinflammation seems to play a critical role in the pathogenesis of AD. Inflammatory processes in the brain are mainly mediated by the intrinsic innate immune system consisting of astrocytes and microglial cells, and cytokine, chemokine, and growth factor signaling molecules. However mounting evidence suggest that the Central Nervous System (CNS) is accessible to lymphocytes and monocytes from the blood stream, indicating that there is an intense crosstalk between the immune and the CN systems. On the other hand, some AD-specific brain-derived proteins or metabolites may enter the plasma through a deficient blood-brain barrier, and exert some measurable signaling properties in peripheral cells. The goals of this review are: 1) to explore the evidences of changes in signaling pathways that could mediate both central and peripheral manifestations of AD, and 2) to explore whether changes in immune cells, particularly lymphocytes, could contribute to AD pathogenesis.
Keywords: mitochondrial dysfunction